2020
DOI: 10.1177/0013916520937453
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Care and Neighborhood Bonds: An Unequal Relationship

Abstract: Research in environmental psychology has found a positive relationship between place bonds and behaviors related to care and maintenance of place. Although this relationship has been analyzed in natural environments, it has been less frequently studied in urban environments and has yielded contradictory results. The aim of this study is to analyze behavior related to care and conservation of neighborhood and its possible relationship to place bonds, as well as to other variables that we think may be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
1
5
0
2
Order By: Relevance
“…Furthermore, in the best conserved villages in the state of Iowa in the USA, a high degree of community attachment has also been observed (Rice & Miller, 1999). Hidalgo et al (2020) confirm that neighbourhood attachment is positively correlated, albeit only moderately, with taking care of the neighbourhood and that individual characteristics and not neighbourhood characteristics explain this relationship. In particular, they have shown that the relationship between attachment and taking care of the neighbourhood is moderated by the socio-economic level of residents.…”
Section: How Does Place Attachment Influence Behaviour?mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, in the best conserved villages in the state of Iowa in the USA, a high degree of community attachment has also been observed (Rice & Miller, 1999). Hidalgo et al (2020) confirm that neighbourhood attachment is positively correlated, albeit only moderately, with taking care of the neighbourhood and that individual characteristics and not neighbourhood characteristics explain this relationship. In particular, they have shown that the relationship between attachment and taking care of the neighbourhood is moderated by the socio-economic level of residents.…”
Section: How Does Place Attachment Influence Behaviour?mentioning
confidence: 99%
“…While community participation, participation in conservation and awareness campaigns or the management of neighbourhood problems are ways of taking care of where we live, there are other direct ways of protecting or caring for urban public spaces that aim to contribute to optimal physical conservation. In particular, as Hidalgo et al (2020) point out, these are actions that are carried out directly, intentionally and in a localized way in the neighbourhood with the explicit intention of conserving and maintaining the physical space of the neighbourhood. Such behaviours include respecting green spaces and urban furniture, disposing of rubbish in bins and cleaning up dogs’ mess.…”
Section: How Does Place Attachment Influence Behaviour?mentioning
confidence: 99%
See 2 more Smart Citations
“…Hidalgo et al (2021) discovered a positive and significant relationship between neighbourhood attachment and neighbourhood care, although the strength of this relationship was not particularly strong. Another study (Hosany et al, 2020), surveying 410 prospective Spanish tourists investigated the predictors of visit intention, hypothesizing that ad-evoked positive affect, place attachment, and motivation would play a role.…”
Section: Place Attachment and Behavioural Intentionmentioning
confidence: 99%